Decision-making in foreign policy - Partowazar, Baharak; Jawan, Jayum; Soltani, Fakhreddin (Espaces Marx, 2014)
Process of decision-making in foreign policy depends on different factors. Through considering factors of decision-making in foreign policy, national leaders use a set of rules to apply to different situations when they deal with international affairs. There are two approaches that influence process of decision-making. The first one is external factors that limit the choices of states regardless of their political system, history and culture. In other words external factors refer to systemic pressures of international relations that affect behavior of all states in process of foreign policy decision-making. The second one is internal factors that refer to various viewpoints and set of expectations in domestic environment of the states. In other words, despite to the same systemic pressures, states behave differently because their internal sources such as different political systems, cultures, and leaders influence their reactions to systemic pressures. After explaining meanings of foreign policy and decision-making, this article tends to review the external and internal factors of decision-making and explain how they influence process of foreign policy.